The Role of Accounting Mechanisms for Corporate Governance in Reducing Creative Accounting Practices in Telecommunications Sector Companies in Riyadh City: An Empirical Study - Banasser, Lamis Jameel; Alsayegh, Maha Faisal (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aimed to identify the role of accounting mechanisms for corporate governance in reducing creative accounting practices in telecommunications sector companies in Riyadh city. A descriptive analytical approach was followed to conduct the field study. Sample of the study consisted of members of the audit committee, internal auditors, accountants from the surveyed telecommunications’ sector companies, and the external auditors in the audit offices that specialized on auditing the examined sample of companies. Questionnaire was used as a data collection method.Results showed that activating the role of accounting mechanisms for corporate governance can greatly contribute in limiting creative accounting practices. As they are controlling mechanisms that capable of protecting companies, shareholders and stakeholders from any manipulation or misleading information in the financial statements. Further, internal audit plays a major role in limiting creative accounting practices by examining and evaluating the effectiveness of the internal control system. Furthermore, the independence and competence of the external auditor and his commitment to the rules of conduct and ethics of the profession contribute greatly in limiting creative accounting practices in the examined companies. The study recommended the necessity of holding specialized training courses for members of audit committees, internal auditors and external auditors on methods of detecting creative accounting practices to combat and reduce them.
Keywords: creative accounting; corporate governance mechanisms; internal audit; external audit; audit committees